Video laryngoscopy is associated with improved first‐pass intubation success compared with direct laryngoscopy in emergency department trauma patients. Issue 1 (22nd January 2021) - Li, Timmy; Jafari, Daniel; Meyer, Cristy; Voroba, Ashley; Haddad, Ghania; Abecassis, Samuel; Bank, Matthew; Dym, Akiva; Naqvi, Ali; Gujral, Rashmeet; Rolston, Daniel
Abstract: Objective: We aimed to assess differences in (1) first‐pass intubation success, (2) frequency of a hypoxic event, and (3) time from decision to intubate to successful intubation among direct laryngoscopy (DL) versus video laryngoscopy (VL) intubations in emergency department (ED) patients with traumatic injuries. Methods: This retrospective cohort study was performed at a Level I trauma center ED where trauma activations are video recorded. All patients requiring a Level I trauma activation and intubation from 2016 through 2019 were included. Multivariable logistic regression was used to assess the association between initial method of intubation and first‐pass success. Differences in frequency of a hypoxic event and time to successful intubation were assessed using bivariate tests. Results: Of 164 patients, 68 (41.5%) were initially intubated via DL and 96 (58.5%) were initially intubated via VL. First‐pass success for DL and VL were 63.2% and 79.2%, respectively. In multivariable regression analysis, VL was associated with higher odds of first‐pass intubation success compared with DL (odds ratio: 2.28; 95% confidence interval: 1.04, 4.98), independent of mechanism of injury, presence of airway hemorrhage or obstruction, and experience of intubator. Frequency of a hypoxic event during intubation was not significantly different (13.2% for DL and 7.3% VL; P = 0.1720). Median time from decision to intubate to successful intubation was 7 minutes for both methods. Conclusions: Video laryngoscopy, compared with direct laryngoscopy, was associated with higher odds of first‐pass intubation success among a sample of ED trauma patients. Frequency of a hypoxic event during intubation and time to successful intubation was not significantly different between the 2 intubation methods.